The psychology of morbid curiosity: Development and initial validation of the morbid curiosity scale. (December 2021) - Scrivner, Coltan
Abstract: The success of horror films, popularity of true crime, and prevalence of violence in the news implies that morbid curiosity is a common psychological trait. However, research on morbid curiosity is largely absent from the psychological literature. In this paper, I present a psychometric tool for assessing morbid curiosity, defined as a motivation to seek out information about dangerous phenomena, and use it to investigate the psychological nature of morbid curiosity. In studies 1 and 2 (ntotal = 1370), the Morbid Curiosity Scale was developed and its relationship to personality was assessed. Morbidly curious individuals were rebellious, socially curious, and low in animal reminder disgust. Study 3 ( n = 317) demonstrated that trait morbid curiosity is stable over 4–6 weeks and that morbidly curious individuals prefer movies where threat is a central theme. In Study 4 ( n = 137), participants were presented with a choice between morbid information and non-morbid information (image and text). Morbid curiosity predicted over half the variance ( r 2 = 0.53) in decisions to further investigate morbid information. These four studies provide evidence that morbid curiosity is a normally occurring psychological trait that can be assessed using the new 24-item Morbid Curiosity Scale. Highlights: Morbid entertainment and news topics suggest humans are morbidly curious. The 24-item Morbid Curiosity Scale can be used to assess trait morbid curiosity. Morbid curiosity is a stable and distinct individual difference. Morbidly curious people prefer entertainment with threat as a central theme. Scores on the Morbid Curiosity Scale strongly predict morbidly curious behavior.